Writing on a computer and using paper and pencil: is there any difference in the internal cognitive processes? - Hoomanfard, Mohammad Hamed; Meshkat, Maryam (Penerbit UKM, 2015)
The present study attempted to unveil the differences in the cognitive processes employed in writing in a second language while writing on computer, and with paper and pencil. In doing so, eleven upper-intermediate, Persian-speaking English Language learners wrote texts in response to two International English Language Testing System (IELTS) writing tasks on computer and with paper and pencil. The Cognitive Processes Questionnaire (Weir, et al., 2007) and stimulated recall interviews were employed to collect data. The quantitative and qualitative analysis of the collected data indicated that the participants spent less time on pre-writing planning, in the computerized condition, but they paused more often during the writing process for online planning. Furthermore, the participants, in both conditions, spent less time for planning when they wanted to write examples pertinent to their own life experience. The participants, in the computerized writing, tended to evaluate and review the text during the process writing, while in the paper and pencil condition, the evaluation was postponed to the end of the writing process. Longer text revision and a higher number of the rearrangements of sentences and ideas were other features of computerized writing. These findings along with those of other studies can deepen our understanding of second language writing cognitive processes which can benefit second language teachers, curriculum developers, and test developers.